Reducing Suicide-Related Stigma through Peer-to-Peer School-Based Suicide Prevention Programming. Issue 4 (18th August 2022) - Wright-Berryman, Jennifer L; Thompson, Devyn; Cramer, Robert J
Abstract: Youth suicide rates have consistently risen over the past decade, and stigma related to mental health may create a barrier to young people seeking help. Schools are a common intercept point for mental health and suicide prevention programming. Hope Squad, a school-based, peer-to-peer, suicide prevention program, uses trained and mentored students nominated by their peers to perform intentional outreach with fellow students. When a Hope Squad member detects a mental health or suicide crisis in a peer, they alert a trusted adult. We employed a cohort, wait-list–control, cross-sectional survey design. We recruited more than 3, 400 students from nine schools—five with Hope Squads and four without—to observe differences in student-body suicide-related stigma. At the end of the academic year, there was significantly lower stigma in Hope Squad schools versus those without the program. Findings suggest that a peer-to-peer, school-based, suicide prevention program may reduce stigmatizing attitudes related to suicide. Next steps include a randomized controlled trial to identify changes in help-seeking and similar protective factors.